INDIGENOUS BACILLUS SPECIES ISOLATED FROM AEDES AEGYPTI LARVAE: ISOLATION, LARVICIDAL TOXICITY SCREENING, PHENOTYPIC CHARACTERIZATION, AND MOLECULAR IDENTIFICATION - Salamun; Rizky Danang Susetyo; Hakimatul Husniyah; Almando Geraldi; Ni’matuzahroh; Fatimah; Farah Aisyah Nafidiastri; Nabilatun Nisa’; Salamy, Muhammad Fath Alhaqqi Sanis (BIOTROPIA, 2023)
Vector-borne diseases transmitted by mosquitoes are considered a significant public health problem worldwide. Aedes aegypti is one of the mosquito species responsible for transmitting these diseases. One environmentally friendly method of vector control is the use of microbial agents such as Bacillus species. This study aimed to explore investigate indigenous entomopathogenic bacteria of Bacillus species isolated from A. aegypti larvae. Larvae samples were collected from breeding sites of A. aegypti. All isolates underwent screening and affirmation confirmation tests to assess their larvicidal toxicity against A. aegypti larvae. Phenotypic characterizations and molecular identifications were conducted to determine the species of the Bacillus isolates based on similarity index and percent identity (%ID). Phylogenetic trees were used to compare the isolates with other Bacillus species. The results revealed 120 isolates of Bacillus species from A. aegypti larvae samples. Among them, three isolates (LS3.3, LS9.1, and LSD4.2) exhibited the highest larvicidal toxicity in the confirmation test, resulting in larval mortality rates of 100%, 96.7%, and 100%, respectively, after 48 hours of exposure. Molecular identifications, showed that LSD4.2 had a 99.16% ID with Bacillus velezensis, LS3.3 had a 98.22% ID with Bacillus mojavensis, and LS9.1 had a 99.93% ID with Bacillus subtilis. These three bacteria from the Bacillus genus have been reported to offer significant benefits to humans.